2013
DOI: 10.1016/j.compositesb.2012.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fiber treatment on morphology, tensile and thermogravimetric analysis of oil palm empty fruit bunches fibers

Abstract: The objective of this study was to evaluate the effect of fiber treatment on both morphological and single fiber tensile strength of empty fruit bunch (EFB). EFB fiber was treated with boiling water, 2% sodium hydroxide (NaOH) and combination both NaOH and boiling water. Fiber morphology was characterized by scanning electron microscopy (SEM). Thermogravimetric analysis (TGA) was further used to measure the amount and rate of change in the weight (weight loss) of treated fiber as a function of temperature. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(93 citation statements)
references
References 35 publications
5
87
1
Order By: Relevance
“…Norul Izani et al (2013) reported that the tensile strength and elastic modulus of NaOH pre-treated fibres were higher than those of untreated fibres; however, these findings contradicted the results reported by Nishiyama and Okano (1998), who found that the tensile strength of the fibres decreased after alkali pre-treatment. Moreover, the exact mechanical behaviour of OPSF is still not clear; it can be either viscoelastic or viscoplastic, in which the former has been reported by Sreekala et al (2001b).…”
Section: Introductioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Norul Izani et al (2013) reported that the tensile strength and elastic modulus of NaOH pre-treated fibres were higher than those of untreated fibres; however, these findings contradicted the results reported by Nishiyama and Okano (1998), who found that the tensile strength of the fibres decreased after alkali pre-treatment. Moreover, the exact mechanical behaviour of OPSF is still not clear; it can be either viscoelastic or viscoplastic, in which the former has been reported by Sreekala et al (2001b).…”
Section: Introductioncontrasting
confidence: 57%
“…This indicates that both the waxy layer and silica bodies are less resistant to alkali pre-treatment. The absence of these surface impurities (waxy layer and silica bodies) has been claimed to improve the fibre-matrix adhesion through better bonding or interface, as reported in previous studies (Norul Izani et al 2013;Shalwan and Yousif 2014;Mahjoub et al 2014). No significant microstructural changes were observed for fibres pre-treated by 10 to 30% w/v NaOH concentrations; however, at 40% w/v NaOH concentration, the internal structure of the fibre was revealed (Figs.…”
Section: Microstructure Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…The specimens were left to cure within the mould at 25 °C for 12 h. Subsequently, post curing was conducted in an oven at 80 °C for 2 h, under air circulation [13]. Finally, rectangular plates with dimensions of 300 × 300 × (3.2 ± 0.4) mm 3 were produced. The plates were then cut using a Dremel 4000 tool to produce specimens for mechanical testing, in accordance with the related standards.…”
Section: Composite Preparationmentioning
confidence: 99%
“…This has generated increased interest in the development of natural fibre-reinforced composites [2][3][4]. Natural fibre-reinforced composites use plant-based natural fibres, such as Pennisetum purpureum, jute, hemp, flax, kenaf, and sisal [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%